Evaluation index and evolution law of fault sealing in caprock above depleted reservoir - Kai Zhao; Xiaoyun Wang; Wenjie Song; Zhihui Xu; Shuyi Shi; Simin Zhang; Chenxi Yang (International Journal of Coal Science & Technology)
Abstract In the process of oil and gas production, reservoir pressure depletion leads to changes in pore pressure and in-situ stress in caprock, which may reactivate closed faults in caprock, break the sealing of caprock, and make depleted oil and gas reservoirs unsuitable for gas storage. In order to effectively evaluate the sealing of faults in caprock above depleted reservoir and provide a basis for a reasonable selection of injection time and location for gas storage, this paper comprehensively considers fault slip potential (FSP) and fault tensile potential (FTP), and establishes a fault sealing evaluation model in caprock above depleted reservoir. The influences of distance of fault from reservoir top, reservoir pressure depletion degree, cap mechanical property, fault occurrence, fault frictional property and in-situ stress anisotropy in caprock on different types of FSP and FTP are analyzed. The results show that for normal faults, reverse faults, and strike-slip faults, FTP increases with reservoir depletion and does not cause tensile failure, among which FTP is the smallest for normal faults. FSP is the key to controlling fault sealing in caprock above depleted reservoir. For reverse faults and strike-slip faults, in the early stage of reservoir depletion, the FSP is larger when the fault is farther away from the top of the reservoir, while normal faults are the opposite. When the normal fault is closer to the top of the reservoir, the cap poisson ratio is smaller, the Biot’s coefficient is larger, the internal friction coefficient of the fault is smaller, the inherent shear strength of the fault is smaller, $$\frac{{σ_\text{H} }}{{σ_{{\text{v}}} }}$$ σ H σ v is smaller, $$\frac{{σ_{{\text{h}}} }}{{σ_{{\text{v}}} }}$$ σ h σ v is smaller, $$45^° < β < 75^°$$ 45 ∘ < β < 75 ∘ , $$α = 0^°$$ α = 0 ∘ or $$α = 180^°$$ α = 180 ∘ , the FSP is larger with the reservoir depletion, and the shear failure of the fault is the most likely. At this time, the reservoir pressure should be strictly controlled not to be too small, so that it can be suitable for the construction of gas storage. Under other conditions, the possibility of shear failure of the caprock is less. For reverse faults and strike-slip faults, when $$\frac{{σ_\text{H} }}{{σ_{{\text{v}}} }}$$ σ H σ v is smaller, the FSP decreases first and then increases with reservoir depletion. Although the possibility of shear failure decreases in the initial stage of reservoir depletion, it increases in the later stage. The research results can provide a theoretical basis for the reconstruction of underground gas storage.